Intersectionality, equity-mindedness, and access to care - Nishi, Naomi W.; Watley, Erin; Collier, Mary Jane; Morales, Gabriela I. (Frontiers in Veterinary Science, 2025)
The factors that contribute to an individual’s and/or community’s access to veterinary care for their animal(s) are manifold. While some (potential) clients must navigate barriers, including transportation options, time off during business hours, physical access, cost of care, and language barriers, there are also identity factors and experiences that affect access to veterinary care particularly for people whose identities are marginalized. These include clients experiencing distrust and/or disrespect in their interactions with veterinary professionals. We explore how intersectionality affects access to veterinary care, especially for those who are multiply marginalized by societal systems of oppression. We share research findings on the experiences of clients that identify as women of color and/or non-binary people of color that have had to navigate barriers to their access to veterinary care, including through broken trust and experienced disrespect. We then define and propose strategies for engaging intersectional equity-mindedness in clinical practice. We connect these concepts of intersectionality and equity-mindedness to their implications for access to care.